2017
DOI: 10.1111/dgd.12371
|View full text |Cite
|
Sign up to set email alerts
|

Developing guinea pig brain as a model for cortical folding

Abstract: The cerebral cortex in mammals, the neocortex specifically, is highly diverse among species with respect to its size and morphology, likely reflecting the immense adaptiveness of this lineage. In particular, the pattern and number of convoluted ridges and fissures, called gyri and sulci, respectively, on the surface of the cortex are variable among species and even individuals. However, little is known about the mechanism of cortical folding, although there have been several hypotheses proposed. Recent studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 85 publications
3
15
0
Order By: Relevance
“…An important finding regarding the role of Insm1 in promoting neurogenesis was that upon Isnm1 overexpression in embryonic mouse neocortex, about 40% of the BPs were bRGCs [ 73 , 74 ]. This is consistent with a possible role of Insm1 in the expansion of the neocortex, as bRGCs are the principal neuron-producing NPC type in species with an expanded neocortex [ 16 , 17 , 19 , 26 , 30 , 31 , 65 ].…”
Section: Transcriptional Programs That Regulate Neocortical Neurogsupporting
confidence: 82%
See 1 more Smart Citation
“…An important finding regarding the role of Insm1 in promoting neurogenesis was that upon Isnm1 overexpression in embryonic mouse neocortex, about 40% of the BPs were bRGCs [ 73 , 74 ]. This is consistent with a possible role of Insm1 in the expansion of the neocortex, as bRGCs are the principal neuron-producing NPC type in species with an expanded neocortex [ 16 , 17 , 19 , 26 , 30 , 31 , 65 ].…”
Section: Transcriptional Programs That Regulate Neocortical Neurogsupporting
confidence: 82%
“…Interestingly, the same Pax6 downstream targets (e.g., Ngn2 and Tbr2 ) negatively regulate Pax6 expression to drive neuronal differentiation [ 13 , 58 , 59 , 60 ]. However, in contrast to the mouse, Pax6 expression is maintained in the BPs of species with an expanded neocortex [ 16 , 17 , 19 , 26 , 31 , 56 , 61 , 62 , 63 , 64 , 65 ]. How BPs in gyrencephalic species are able to maintain Pax6 expression is not known.…”
Section: Transcriptional Programs That Regulate Neocortical Neurogmentioning
confidence: 99%
“…In the guinea pig neocortex, the number of Tbr2+ NPCs reaches minimum values, not before day 50 p.c., suggesting neurogenesis to end between day 40 and 50 p.c. (Figures 2F, 3D), which is slightly later when compared with a previous study (Hatakeyama et al, 2017). Extrapolation of the Tbr2+ NPCs abundance in the SVZ of both species revealed their minimum value to be generated around 30 p.c.…”
Section: Developmental Differences In Neurogenesis Between the Dwarf Rabbit And Guinea Pig Neocortexmentioning
confidence: 45%
“…Hatakeyama et al . () introduce the guinea pig brain as a model system to study mechanisms and principles of cortical folding.…”
mentioning
confidence: 99%
“…Noguchi et al (2017) studied Sema3A expression in embryos of Chinese soft-shelled turtle, chick, ocelot gecko and mouse, and indicated that Sema3A plays a crucial role for neurolal network formation. Hatakeyama et al (2017) introduce the guinea pig brain as a model system to study mechanisms and principles of cortical folding.…”
mentioning
confidence: 99%